URDIMBRAR: Transdisciplinary performance theater play (The Voz a Vos Bulletin, 2023)
Urdimbrar is a transdisciplinary play of performative theater that aims to circulate the voices of LGBTIQ+ victims. To do this, three testimonies present in the Testimonial Volume of the CEV final report, published in 2022, were taken as a starting point. Five bodies on stage dance, sing, face each other, fall and get up, but above all, they express their voice of resistance to a society that has sedimented heteropatriarchal logics that have become death and annihilation. However Warping is not only lament - although it is appropriate to be so in this withered society - it is also a proposal to establish strong ties as a basis for the social fabric. Weaving is a call to action, to look at each other's faces, to feel our bodies, to recognize our differences.
Keywords: Play; LGBTIQ+; Dramaturgy; Social